Multi-dimensional poverty estimates for fishing households in the south-western zone of Nigeria (2013)
Using the traditional income-expenditure approach, coastal households have been adjudged to be poorer than their non-coastal counterparts. Poverty encompasses deprivation in other welfare dimensions such as education, health, housing, household assets, potable water and social participation. However, only few studies have conceptualised poverty with these various dimensions in focus. Hence, the nature and determinants of multi-dimensional poverty among fishing households in southwestern Nigeria were investigated. A multi-stage sampling procedure was adopted in collecting data from fishing households using structured questionnaire. Three coastal states (Ogun, Ondo and Lagos) were selected at the first stage. The three Local Government Areas (LGAs) with coastal characteristics were selected in Ogun and Ondo states while in Lagos state, three of such LGAs were randomly selected at the second stage. Subsequently, 100 coastal communities and 500 fishing households were selected based on probability proportionate to size. Data were obtained on socio-demographic characteristics and thirteen poverty dimensional variables including household expenditure, assets, housing quality, sources of drinking water and lighting, types of cooking fuel, waste disposal methods, and participation in grassroot politics and community development projects. Data were analysed using descriptive statistics, multiple correspondence analysis, Alkire-Foster counting and dimension-adjusted poverty measure and logit regression at p = 0.05. Mean age and year of schooling of household heads were 46.0 ± 10.9 and 9.0 ± 4.0 years respectively. Household size and dependency ratio were 5.0 ± 3.0 persons and 0.4 ± 0.4, respectively. Majority (72.1%) of the households were male-headed with 33.7% of houses built onshore. Thirty seven percent (37%) of the houses were built with planks and bamboo with 47.5% of the households defecating directly into the river. Daily mean per capita household income was N1237.20 ± 776.60. Most households (97.5%) had no access to potable water and 60.0% lacked essential household assets. A multi-dimensional poverty cut-off value of 8 was obtained out of a possible 13 welfare indicators that had direct effect on the welfare status of the households. Poverty headcount ratio was 0.6 while the dimension-adjusted poverty incidence, depth and severity were 34.2%, 16.0% and 7.6% respectively. Large-sized households (> 12 members) had higher Poverty Incidence (PI) (0.5938) than small-sized households (< 6 members) with PI of 0.3326, while households with tertiary education had lower PI (0.3351) than those without formal education (0.3781). Households with higher dependency ratio of 0.60 had higher PI of 0.4196 than those with lower dependency ratio of 0.10 having PI of 0.3326. Being fully engaged in onshore economic activities (0.13), using dugout canoes (0.11), and having house located onshores (3.13) increased the probability of households’ multi-dimensional poverty while high educational attainment (- 0.005), income (- 0.14) and land size (- 0.11) reduced it. Multi-dimensional poverty was high among the fishing households. Inadequate education, insufficient income, use of dugout canoes and living onshore increased multidimensional poverty incidence among the households. Reduction in the poverty incidence of households would be achieved through improved access to formal education and use of motorised canoes.